2015
DOI: 10.1007/s10896-015-9775-x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Reflective Functioning to Parent Child Interactions in a Sample of Fathers with Concurrent Intimate Partner Violence Perpetration and Substance Abuse Problems

Abstract: This study is the first to examine reflective functioning (RF) and direct parent-child interactions of fathers with concurrent intimate partner violence (IPV) perpetration and substance abuse (SA) problems. Twenty-four fathers, with children between the age of one and seven, completed a structured interview to assess RF, self-report measures of hostile-aggressive parenting behaviors, IPV perpetration severity, SA severity, and a coded play session with their children. Results of three simultaneous multiple reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…In this review, the majority of the researchers measured the children’s behavioral problems or the parents’ lack of parenting practices in order to determine the harmful influences on the child’s well-being. For example, parenting stress (Overbeek et al, 2017); the child’s reactions and emotional responses after father–child contact (Kita, Haruna, Yamaji, Matsuzaki, & Kamibeppu, 2017); fathering practices, fathers’ severe substance abuse, and violent behavior toward their partners (Stover & Coates, 2016); the child internalizing and externalizing problems (Hunter & Graham-Bermann, 2013); and the father’s participation in domestic violence perpetrator interventions (Alderson, Kelly, & Westmarland, 2013) were reported as key factors and conditions that were measured by the researchers in order to examine how the fathers’ contact influenced child well-being in a family context. It is sometimes uncertain whether these criteria can be confidently classified as either supportive or detrimental to a child’s well-being.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, the majority of the researchers measured the children’s behavioral problems or the parents’ lack of parenting practices in order to determine the harmful influences on the child’s well-being. For example, parenting stress (Overbeek et al, 2017); the child’s reactions and emotional responses after father–child contact (Kita, Haruna, Yamaji, Matsuzaki, & Kamibeppu, 2017); fathering practices, fathers’ severe substance abuse, and violent behavior toward their partners (Stover & Coates, 2016); the child internalizing and externalizing problems (Hunter & Graham-Bermann, 2013); and the father’s participation in domestic violence perpetrator interventions (Alderson, Kelly, & Westmarland, 2013) were reported as key factors and conditions that were measured by the researchers in order to examine how the fathers’ contact influenced child well-being in a family context. It is sometimes uncertain whether these criteria can be confidently classified as either supportive or detrimental to a child’s well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Despite studies consistently reporting the relationship between parenting stress and child adjustment of mother survivors of partner violence (Grych, Raynor, & Fosco, 2004; Holden & Ritchie, 1991; Owen, Thompson, & Kaslow, 2006) and the importance of interventions for positive mother–child interactions after domestic violence (Hegarty, Tarzia, Hooker, & Taft, 2016; Stover & Morgos, 2013), the influence of perpetrator interventions on the positive parenting skills among fathers who use violence in their intimate relationship is less recognized (Alderson, Westmarland, & Kelly, 2013; Featherstone & Fraser, 2012; Scott & Crooks, 2007; Stover & Coates, 2016). Insufficient recognition of the interventions for perpetrators’ parenting practices might be related to the social workers’ inadequate engagement with fathers who use violence.…”
mentioning
confidence: 99%
“…The goal of this intervention is to make each parent an active protagonist able to collaborate, support, trust, and legitimize each other in their parental role. This process of acknowledgment and legitimization of the other is possible only by working to strengthen capacities for mentalization and reflective functioning (Aschieri et al, 2016 ; Stover and Coates, 2016 ). This increase the possibility that the partners will acknowledge their own part of the responsibility for the conflict and the violence, and thus initiate actions aimed at a constructive management of the conflict itself, finding the resources needed to care for the children.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing with each partner what emerges from the preliminary assessment levels is therefore the premise for being able to treat the violence. It is a matter of enhancing each partner's reflective functioning and mentalization capacity, which, we know, are often reduced in violent situations (Stover and Coates, 2016 ). In situations of violence found in separations, the process of elaboration is indispensable for a true emotional separation.…”
Section: Evaluating and Treating Couple Violence Through The Child Cumentioning
confidence: 99%
“…Another complication is that although qualitative studies and clinical descriptions have often emphasized DV fathers' lack of emotional responsivity, results from the handful of published quantitative studies are inconsistent (Stewart and Scott 2014). Stover and Spink, for example, found that domestically violent fathers had limited capacity to think about the thoughts and feelings of their children (Stover and Spink 2012) but that these deficits were unrelated to their parenting or their children's behavior (Stover and Coates 2016).…”
Section: Candidate Mechanisms Of Change For Fathering In the Context Of Domestic Violencementioning
confidence: 99%